Does Positive Illusory Bias Affect Self-Concept and Loneliness in Children With Symptoms of ADHD?. Issue 11 (September 2019) - Capodieci, Agnese; Crisci, Giulia; Mammarella, Irene Cristina
Objective: Positive illusory bias (PIB) has been amply studied in children with ADHD, but its function is still limited understanding.Method: In a sample of 21 children with symptoms of ADHD, this study investigated whether they were more likely to be rejected by peers and examined PIB, and its influence on self-concept and loneliness, comparing the children with symptoms of ADHD with children who had weak social skills, but no ADHD. The children's and teachers' perception of social difficulties were compared, and self-concept and loneliness were analyzed in the two groups, which were also compared with typically developing (TD) children.Results: The results showed the presence of PIB on social skills in children with symptoms of ADHD, but this phenomenon did not give them a higher self-concept, which was similar to that of children with weak social skills and lower than in TD children.Conclusion: The implications of these findings are discussed.